PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SEL DI KELAS XI IPA SMA SWASTA PRAYATNA MEDAN - Laia, Katarina; Amrizal, Amrizal (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
This research aims to determine the effect of the problem-based learning model on student learning outcomes in cell material. This research was conducted in class XI Science at Praayatna Private High School Medan in the 2023/2024 academic year. The sample in this study was class XI IPA consisting of two classes taken by random sampling, namely class XI IPA -2 as the experimental class (with the PBL model) and class This research used a test instrument of 20 multiple choice questions. The data obtained came from the pretest and posttest scores of the experimental class and the control class, pretest scores (average 41.22 and 48.89), posttest scores, (60.37 and 82.26). Data normality test using SPSS and homogeneity test using SPSS and F test. Hypothetical test using t test with a significant value of 0.00 ˂ α = 0.05 so that Ha is accepted and Ho is rejected. Based on the results of this research analysis, the overall differences in learning models used show that the PBL learning model as an experimental model is better than the conventional learning model used. In other words, overall, the use of the PBL learning model makes a very big difference, there is an increase in students' biology learning outcomes in cell material